Effects of Self-Control on Cheating Among Indonesian College Students - Gloryka Ednadita; Shierlen Octavia; Farah Safira Khairunnisa; Isyah Rodhiyah; Dwiki Hendraputra (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2020)
Cheating among college students has long been a concern in the academic field. In addressing this problem, it is imperative to determine in what circumstances college students cheat. Looking into the internal factor, previous research found that the depletion of self-control increased the probability of cheating. To determine whether this result could be replicated in an Indonesian population, we conducted an experimental study. A sample of 63 undergraduates was randomized into two groups, a self-control depletion group (had difficult essay-writing task) and a self-control no-depletion group (had an easy essay-writing task). After writing the essay, the participants were then asked to complete a knowledge task directly on the test sheet and then copy their answers into a pre-marked sheet. Cheating was determined as modified answers from the test sheet to the pre-marked sheet. The results showed a significant difference in modified answers between the depleted and non-depleted self-control group (t = 2.09, p < 0.05). This finding indicates that depletion of self-control affects cheating. This study has a meaningful implication for determining the ideal setting in which the university should conduct their examinations.